FINANCIAL LITERACY AND FINANCIAL INCLUSION ON THE FINANCIAL PLANNING OF THE CITY OF PALEMBANG - Fitriah, Wani (International Business Management - Universitas Ciputra, 2021)
The formulation of the problem in this study was is there the influence of financial literacy and financial inclusion on the financial planning of the people of Palembang. This study aimed to determine the influence of finacial literacy and finacial inclusion on the financial planning of the city of the Palembang. In this research used infinite population and the number of sample was 200 respondents. The data used in this study was primary data. The technique used for collecting the data was questionnaire. At the analysis stage used is qualitative data quantitative. The analysis technique used was the test instrument consisting of validity and reliability tests, while the data analysis techniques were descriptive and inferential statistics in the form of a classic assumption test (normality test and multicolliniarity test), multiple linear regression analysis, hypothesis testing (F test and t test ) and the coefficient of determination. The results showed that based on the F test (together) for financial literacy and financial inclusion variables had a positive and significant effect on the financial planning of the people of Palembang. While the results of the t test (individually) the financial literacy variable had a positive and significant influence on the financial planning of the people of Palembang. While the financial inclusion variable had no influence and no significant on the financial planning of the Palembang city community.